Three-Dimensional–Printed Laboratory-on-a-Chip With Microelectronics and Silicon Integration. Issue 2 (June 2017) - Thomas, Daniel J.; McCall, Caitlin; Tehrani, Zari; Claypole, Tim C.
Abstract : Abstract: In this research, an integrated three-dimensional (3D)–printed laboratory-on-a-chip system was developed based on integrating conventional silicon biosensing systems with silver screen–printed electronics. It was discovered that by integrating 220-μm width microchannels, fabricated using 3D-printed polymers, it would offer a means for the development of a microfluidic device with the further possibility for electrically integrating different elements through depositing screen-printed silver contacts. The objective was to achieve low resistance and high reliability with low cost for manufacturing 3D-printed point-of-care diagnostic devices.